2011
DOI: 10.1158/1078-0432.ccr-10-2666
|View full text |Cite
|
Sign up to set email alerts
|

EGF61 Polymorphism Predicts Complete Pathologic Response to Cetuximab-Based Chemoradiation Independent of KRAS Status in Locally Advanced Rectal Cancer Patients

Abstract: Background Cetuximab has demonstrated significant clinical activity in metastatic colon cancer. However, cetuximab-containing neoadjuvant chemoradiation has not been shown to improve tumor response in locally advanced rectal cancer patients in recent phase I/II trials. We evaluated functional germline polymorphisms of genes involved in EGFR pathway, angiogenesis, ADCC, DNA repair, and drug metabolism, for their potential role as molecular predictors for clinical outcome in locally advanced rectal cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…Peter etal found that no significant associations were detected between rs861539 and the response in rectal cancer patients treated with neoadjuvant chemoradiation (Grimminger et al, 2010). Other studies have found no data are available up to date on the effect of rs861539 on tumor response to radiation (Hu-Lieskovan et al, 2011). Meta-analysis found that rs861539 is not association with rectal cancer with radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Peter etal found that no significant associations were detected between rs861539 and the response in rectal cancer patients treated with neoadjuvant chemoradiation (Grimminger et al, 2010). Other studies have found no data are available up to date on the effect of rs861539 on tumor response to radiation (Hu-Lieskovan et al, 2011). Meta-analysis found that rs861539 is not association with rectal cancer with radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation of these results is the different effect of increased EGF activity in different stages of cancer development and possibility of EGFinducing apoptosis or increase of cancer susceptibility to treatment. In this respect, recent studies showing the complete pathological response of advanced rectal cancer patients treated with cetuximab-based neoadjuvant chemoradiation were strongly associated with EGF G allele suggesting possible enhanced inhibition of EGFR pathway or increased sensitivity to radiation therapy [62]. The protective role of EGF 61G allele may suggest also possible influence of the 61A allele that might be masked by the presence of other as-yet unidentified causal genes involved in CRC development.…”
Section: Product Of Pcr-rflp Analysis Of Egf A61g (Left) and P53 Arg7mentioning
confidence: 93%
“…13 This SNP has been associated with the outcome in mCRC patients treated with cetuximab-based therapy. 14,15 Although EGF is the natural ligand of EGFR, other members of the EGF family, such as amphiregulin (AREG) and epiregulin (EREG), can bind to this receptor. 16 The study of these ligands as biological markers has evolved around expression studies measured by immunohistochemical staining and mRNA levels.…”
Section: Introductionmentioning
confidence: 99%